A standardized scoring method for measuring white cast of mineral sunscreens and improving user compliance across diverse skin tones - Alexandra M. Maldonado López; Emily A. Gallagher; Aiden Curry; Kylie Q. Sahloff; Ivan Domicio da Silva Souza (PLoS ONE, 2025)
Introduction Using broad-spectrum sunscreen is an effective practice for preventing skin cancers caused by ultraviolet (UV) radiation. Mineral sunscreens containing zinc oxide (ZnO) and titanium dioxide (TiO2) as physical UV filters are suitable for individuals with sensitive skin or allergies to chemical UV filters. Consumer compliance with sunscreen application depends largely on its cosmetic elegance, especially regarding white cast. Despite this, there is no official method to quantify white cast and help design sunscreens for diverse skin tones. Methods To address this gap, we developed white cast scoring protocols that combine 1) inter-rater reliability (ICC) of expert graders and thirteen study volunteers ranking the white cast produced by ZnO test formulations with 2) objective CIEL*a*b* measurements determined after sunscreen application both in vivo and in vitro. Results Our findings demonstrate a significant correlation between increasing ZnO percentages and higher L* values (whiteness) resulting in a more visible white cast, as assessed by Pearson coefficient in vivo (r ≥ 0.822; p < 0.001) and Kruskal-Wallis (p < 0.0001) with Dunn’s post hoc pairwise comparisons. White cast scores for the ZnO formulations were substantially consistent across both in vivo and in vitro methodologies, with higher ZnO concentrations producing unacceptable levels of white cast. Conclusion This study provides a white cast scoring system, based on subjective white cast perception and L* values, as a quantitative tool for evaluating and refining mineral sunscreen formulations, contributing to developing more cosmetically elegant sunscreens suitable for a wide range of skin tones.